A five-axis tool length compensation method using the numerical control program with macro variable. (July 2015) - Xu, Rufeng; Chen, Zhitong; Meng, Fanjun; Guo, Qianjian
Most of the early five-axis computer numerical control systems do not have the function of five-axis tool length compensation. When the tool length changes in five-axis machining, the original numerical control program will not be able to continue to be utilized. At the moment, the cutter location file needs to be post-processed again to generate the new numerical control program through modifying the value of the pivot length. In order to solve the above problem, this article proposes a five-axis tool length compensation method using the numerical control program with macro variable for five-axis machine tools with dual rotary heads or with a rotary head and table. First, by analyzing the structure of the specific five-axis machine tool, a kinematics model of the five-axis machine tool was established and solved. Second, a post-processor for the five-axis machine tool was developed, and the pivot length as a macro variable was written into the numerical control program through the post-processor. Moreover, the five-axis tool length compensation was implemented by modifying the macro variable of pivot length in the numerical control program. Finally, a turbine blade was machined on a five-axis machine with a rotary head and table, the generated cutter location file was converted into the numerical control program with macro variables by using the proposed method, and the generated numerical control program was simulated on the solid cutting simulation software. Simulated results verify the effectiveness of the proposed method. In addition, the proposed method can be widely applied to early five-axis machine tools without the function of five-axis tool length compensation.